Demography as essential variable in real estate price prognosis - Dąbrowski, Janusz; Hvizdová, Eva; Polačko, Jozef (Geomatics and Environmental Engineering, 2019)
In publications regarding real estate market analysis, one can find a statement that demography has a crucial impact on the real estate market only over the long term. Such a conclusion usually results in disregarding demography as an independent variable of real estate market analysis conducted to assess the value of property. On the example of the Subcarpathian town of Jarosław, the author indicates that demography should nowadays be particularly taken into account when assessing commercial property value. Demographic changes over the last few years have been so substantial that ignoring them in real estate price prognosis would certainly be a huge mistake. Demography does not only mean quantity; it means quality changes as well. A quickly aging society along with the migration of young people to big cities in search of a job has significantly influenced the changes of a consumer´s wallet wealth. Assuming that all other variables describing the real estate market do not impact its value, it can be indicated that demography can be an essential factor that influences statistical reasoning.